Human CD141+ Dendritic Cell and CD1c+ Dendritic Cell Undergo Concordant Early Genetic Programming after Activation in Humanized Mice In Vivo - Minoda, Yoshihito; Virshup, Isaac; Leal Rojas, Ingrid; Haigh, Oscar; Wong, Yide; Miles, John J.; Wells, Christine A.; Radford, Kristen J. (Frontiers in Immunology, 2017)
Human immune cell subsets develop in immunodeficient mice following reconstitution with human CD34+ haematopoietic stem cells. These “humanized” mice are useful models to study human immunology and human-tropic infections, autoimmunity and cancer. However, some human immune cell subsets are unable to fully develop or acquire full functional capacity due to a lack of cross-reactivity of many growth factors and cytokines between species. Conventional dendritic cells (cDC) in mice are categorized into cDC1, which mediate Th1 and CD8+ T cell responses, and cDC2, which mediate Th2 and Th17 responses. The likely human equivalents are CD141+ DC and CD1c+ DC subsets for mouse cDC1 and cDC2 respectively, but the extent of any interspecies differences is poorly characterized. Here we exploit the fact that human CD141+ DC and CD1c+ DC develop in humanized mice, to further explore their equivalency in vivo. Global transcriptome analysis of CD141+ DC and CD1c+ DC isolated from humanized mice demonstrated that they closely resemble those in human blood. Activation of DC subsets in vivo, with the TLR3 ligand poly I:C, and the TLR7/8 ligand R848 revealed that a core panel of genes consistent with DC maturation status were upregulated by both subsets. R848 specifically upregulated genes associated with Th17 responses by CD1c+ DC, whilst poly I:C upregulated IFN-λ genes specifically by CD141+ DC. MYCL expression, known to be essential for CD8 + T cell priming by mouse DC, was specifically induced in CD141+ DC after activation. Concomitantly, CD141+ DC were superior to CD1c+ DC in their ability to prime naïve antigen-specific CD8+ T cells. Thus CD141+ DC and CD1c+ DC share a similar activation profiles in vivo but also have induce unique signatures that support specialized roles in CD8+ T cell priming and Th17 responses respectively. In combination, these data demonstrate that humanized mice provide an attractive and tractable model to study human DC in vitro and in vivo.